Evaluation of the rational use of the cytological method in the diagnostics of the breast diseases using the Yokohama system - O. G. Grigoruk; V. K. Ilinskiy; T. A. Moskvina; L. M. Bazulina; E. S. Sigitova; A. S. Stepanova; T. V. Ponomareva; D. A. Tsoy; T. V. Sinkina (Опухоли женской репродуктивной системы)
Retrospective analysis of the usage of fine needle aspiration breast cytolology has been represented in the present work. The potentialities of cytological diagnostics according to Yokohama system with characteristics of C1–C5 categories were estimated. The results of cytological conclusions of 4778 patients with breast lesions who had been examined in the Altay oncological dispensary during the year were studied.  Fine needle aspiration breast cytology was used of outpatients in 89.6 % cases. The largest number of patients  with pathological changes in the breast was noted in category C2 with benign processes (75.7 % of all cases). Difficult cases for cytological study, where the method could not guarantee the accuracy of the diagnosis, belong to the C3 and C4 categories (1.9 % of all cases). The cytological conclusion recommended the compulsory usage of the core biopsy. Malignant tumors were identified in 853 (19.9 %) patients with an indication of the histological type of tumors.Thus, the cytological technique (as a part of Triple test) should be chosen for outpatients with breast diseases using the Yokohama writing system (C1–C5 categories) of fine needle aspiration cytology.